Innovative approaches to improving the management of a sales company ("Journal "U". Economy. Management. Finance.", 2023)
Sales management is one of the key functions of a business that determines its competitiveness and success in the market. In modern conditions, taking into account the rapidly changing business environment and technological innovations, companies face a number of challenges in managing their sales activities. Optimization of processes, application of new methods and tools, as well as improvement of customer interaction are becoming important factors in ensuring the efficiency and effective management of a sales company. This article discusses innovative approaches that can help improve the management of a sales company.
Keywords: sales; company; management; solutions; innovation; competitiveness; personnel; target; business